The influence of electron utilization pathways on photosystem I photochemistry in Synechocystis sp. PCC 6803. Issue 23 (16th May 2022) - Smolinski, Sharon L.; Lubner, Carolyn E.; Guo, Zhanjun; Artz, Jacob H.; Brown, Katherine A.; Mulder, David W.; King, Paul W.
Abstract : Alteration of electron utilization pathways affects PSI reaction center structure and photochemical properties. Abstract : The capacity of cyanobacteria to adapt to highly dynamic photon flux and nutrient availability conditions results from controlled management and use of reducing power, and is a major contributing factor to the efficiency of photosynthesis in aquatic environments. The response to changing conditions includes modulating gene expression and protein–protein interactions that serve to adjust the use of electron flux and mechanisms that control photosynthetic electron transport (PET). In this regard, the photochemical activity of photosystem I (PSI) reaction centers can support balancing of cyclic (CEF) and linear electron flow (LEF), and the coupling of redox carriers for use by electron utilization pathways. Therefore, changes in the utilization of reducing power might be expected to result in compensating changes at PSI as a means to support balance of electron flux. To understand this functional relationship, we investigated the properties of PSI and its photochemical activity in cells that lack flavodiiron 1 catalyzed oxygen reduction activity (ORR1). In the absence of ORR1, the oxygen evolution and consumption rates declined together with a shift in the oligomeric form of PSI towards monomers. The effect of these changes on PSI energy and electron transfer properties was examined in isolated trimer and monomer fractions of PSI reaction centers. Collectively, the results demonstrate that PSI photochemistry is modulated through coordination with the depletion of electron demand in the absence of ORR1.